Assessment of Vitamin D Status in Adults Attending a Tertiary Care Hospital in Dhaka, Bangladesh (Bangladesh Journal of Medicine, 2026)
Background: Vitamin D (Vit D) is a fat-soluble steroid hormone crucial for skeletal health, immune function, and chronic disease prevention. Despite ample sunlight, a high prevalence of hypovitaminosis D has been reported in Bangladesh. This study aimed to determine the prevalence and correlates of Vit D deficiency(VDD) among adults attending a tertiary care facility in Dhaka. Methods: A crosssectional study was conducted at the Bangladesh Institute of Health Sciences (BIHS) General Hospital, Dhaka, from 1st January 2021 to 31st December 2023. A total of 300 adult patients (N=300) meeting inclusion criteria were enrolled. Data on socio-demographics, lifestyle, and clinical presentation were collected via a structured questionnaire. Serum 25-hydroxyvitamin D [25(OH)D] was measured by Chemiluminescent Microparticle Immunoassay (CMIA). Results: The mean age of participants was 38.7±12.4 years, with 54.0% Female and 46.0% male. Hypovitaminosis D (25(OH)D